Peningkatan Kemampuan Menulis Puisi Sederhana Berdasarkan Gambar dalam Pembelajaran Tematik Bahasa Indonesia melalui Model Pembelajaran Examples-Non Examples pada kelas II SD Negeri 3 Linggasari Semester 2 Tahun Pelajaran 2016/ 2017 - Rahayu, Sudi (Jurnal Pancar, 2018)
The purpose of this classroom action research: to improve the ability to write in Indonesian Language thematic learning for class II students, and to find out whether the ability to write simple poetry based on images through Examples Non Examples learning models (analyzing images) can increase. The implementation of this study involved 2 teachers as collaborators in order to make observations on the implementation of learning for all students and teachers, which was carried out in 2 (two) cycles. Each cycle includes stages: 1) preparation 2) planning, 3). Implementation of actions, 4). Observations, and 5). Reflection. The subjects of the study: 2nd semester students of 2nd grade SDN 3 Linggasari UPK Kembaran. The results showed that through learning models Examples Non Examples or analyzing images can improve the ability to write simple poetry based on images for class II students, in the first Cycle? (P1 (81.1%); P2 (83.8%) with criteria is Good ( B), has not met the target, because the target is complete (85%) and the class average (85.0), Second Cycle? P1 (86.5%), P2 (89.2%) with the criteria is Very good (A), so that it has met the complete target (85%) and average (85.0) .The application of the Examples Non Examples learning method can also improve learning completeness in a classical manner, from P1 (81.1%); P2 (83.8%) on the first cycle rose to P1 (86.5%); P2 (89.2%) in the second cycle. The average student learning outcomes increased, in the first cycle (77.1) of P1 (76.6) and P2 (77 , 5) to be (85.1) from P1 (83.7) and P2 (86.6) in the second cycle.